2012
DOI: 10.1371/journal.pone.0041264
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin, an Exogenous Phytomolecule, Enhances Osteogenesis but Not Angiogenesis—An In Vitro Efficacy Study

Abstract: We found that Icaritin, an intestinal metabolite of Epimedium-derived flavonoids (EF) enhanced osteoblastic differentiation of mesenchymal stem cells (MSCs) only under osteogenic induction conditions. We also demonstrated its effect on inhibition of adipogenic differentiation of MSCs. Unlike the findings of others on EF compounds, we showed that Icaritin was unable to promote proliferation, migration and tube like structure formation by human umbilical vein endothelial cells (HUVECs) in vitro. These results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…As an exogenous phytomolecule, ICT is known for its osteogenic potential and stable chemical structure [6,13,16]. Attributed to its bone anabolic effects [6,12,14,16,46], scaffolds incorporating ICT possessed a unique feature of its sustained release where the released ICT molecules still preserved its original bioactivity as confirmed in recent in vitro work [6].…”
Section: Plga/tcp Composite Scaffolds Incorporating Ict For Bone Formmentioning
confidence: 91%
See 1 more Smart Citation
“…As an exogenous phytomolecule, ICT is known for its osteogenic potential and stable chemical structure [6,13,16]. Attributed to its bone anabolic effects [6,12,14,16,46], scaffolds incorporating ICT possessed a unique feature of its sustained release where the released ICT molecules still preserved its original bioactivity as confirmed in recent in vitro work [6].…”
Section: Plga/tcp Composite Scaffolds Incorporating Ict For Bone Formmentioning
confidence: 91%
“…EF is a known ''bone strengthening Chinese herb'' exerting an anabolic effect on osteoporotic bone [14] and promoting angiogenesis attributed to its estrogenic effect [15]. Recent work demonstrated that its metabolite ICT was the potent one to enhance differentiation and proliferation of osteoblasts and facilitate matrix calcification; and meanwhile, ICT was also found to be able to inhibit adipogenic differentiation of mesenchymal stem cells (MSC) [9,11,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Icaritin, a prenylflavonoid derivative from the Chinese tonic herb Epimedium, has been shown to have many pharmacological and biological activities, such as antioxidant activity [1] , enhancement of the osteoblastic differentiation of mesenchymal stem cells [2][3][4] , inhibition of human prostate carcinoma growth [5,6] and neuroprotective effects [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts were identified via staining for ALP and Alizarin Red S staining. ALP activity is used as an early phenotypic marker for mature osteoblasts, while the formation of mineralized nodules is a phenotypic marker for a later stage of osteogenic differentiation (17). The deproteinized and defatted bone materials were processed into small 0.4x0.4x0.4 cm 3 blocks with an average pore size of 623.67±12.31 µm and met the clinical requirements as indicated in the SEM images.…”
Section: Discussionmentioning
confidence: 99%
“…ECM mineralization was determined by Alizarin Red S staining (17). Cells of the 2nd passage growing to confluence on coverslips were further cultured for three weeks and then fixed with 95% ethanol for 10 min.…”
Section: Staining Of Rat Calvarial Osteoblasts For Alkaline Phosphatamentioning
confidence: 99%